2008
DOI: 10.1063/1.2830032
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of α- and β-alanine molecules by ions at Bragg-peak energies

Abstract: The interaction of keV He(+), He(2+), and O(5+) ions with isolated alpha and beta isomers of the amino acid alanine was studied by means of high resolution coincidence time-of-flight mass spectrometry. We observed a strong isomer dependence of characteristic fragmentation channels which manifests in strongly altered branching ratios. Despite the ultrashort initial perturbation by the incoming ion, evidence for molecular rearrangement leading to the formation of H(3)(+) was found. The measured kinetic energies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…The interaction of high energy radiation, electrons, ions and radicals with biomolecules, in particular with the DNA fragments, nucleic purine and pyrimidine bases, phosphate units and deoxyribose sugar, has been extensively studied to uncover effects of primary and secondary particles in radiation damage of living cells and other biological systems [1][2][3][4][5][6]. The secondary electrons, which are produced in large quantities by the primary ionizing particles in the biological material, may cause single-and double strand breaks in the polynucleotides of DNA through site selective cleavage of the molecular bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of high energy radiation, electrons, ions and radicals with biomolecules, in particular with the DNA fragments, nucleic purine and pyrimidine bases, phosphate units and deoxyribose sugar, has been extensively studied to uncover effects of primary and secondary particles in radiation damage of living cells and other biological systems [1][2][3][4][5][6]. The secondary electrons, which are produced in large quantities by the primary ionizing particles in the biological material, may cause single-and double strand breaks in the polynucleotides of DNA through site selective cleavage of the molecular bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[20] This was achieved through the detection of cationsi n coincidence, ap owerful tool to extract time-related information about fragmentationp rocesses. This technique has been appliedt om ultiply ionized amino acids [21,22] and DNA bases.…”
mentioning
confidence: 99%
“…For a-alanine, [7] formation of COOH À or HCOO À (m/z 45) was one of the most dominant channels, whereas for bA it was a rather weak channel. An explanation for this molecule-specific observation may be given by the study reported by Bari et al [1,2] in which CÀC a bond cleavage (leading to the formation of the CH 3 CH(NH 2 )…”
Section: M/z 40 To 45mentioning
confidence: 95%
“…[1,2] Both the intensity and the kinetic energy of the various ionic fragments differ from one isomer to the other.…”
Section: Introductionmentioning
confidence: 99%